2019
DOI: 10.1016/j.jgo.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional trajectories before and after a new cancer diagnosis among community-dwelling older adults

Abstract: Older adults followed distinct functional trajectories in the twelve months before and after cancer diagnosis. Functional trajectory pre-diagnosis, poor physical capability, and incurable stage were independent risk factors for worsening disability post-diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 56 publications
2
28
0
1
Order By: Relevance
“…Previous studies had shown trajectory grouping using the number of disabilities in patients with underlying diseases such as cancer. In a study with cancer patients, the percentage of the severe trajectory group was 21.2% prior to receiving cancer treatment [ 42 ]. Our study is unique in that we show the percentage of the severe disability group (rapidly-deteriorated group) to be around 5.5% in relatively healthy older adults living in rural communities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown trajectory grouping using the number of disabilities in patients with underlying diseases such as cancer. In a study with cancer patients, the percentage of the severe trajectory group was 21.2% prior to receiving cancer treatment [ 42 ]. Our study is unique in that we show the percentage of the severe disability group (rapidly-deteriorated group) to be around 5.5% in relatively healthy older adults living in rural communities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown trajectory grouping using the number of disabilities in patients with underlying diseases such as cancer. In a study with cancer patients, the percentage of the severe trajectory group was 21.2% prior to receiving cancer treatment [41]. Our study is unique in that we show the percentage of the severe disability group (rapidly-deteriorated group) to be around 5.5% in relatively healthy older adults living in rural communities.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies had shown trajectory grouping using the number of disabilities in patients with underlying diseases such as cancer. In a study with cancer patients, the percentage of the severe trajectory group was 21.2 % prior to receiving cancer treatment [42]. Our study is unique in that we show the percentage of the severe disability group (rapidlydeteriorated group) to be around 5.5% in relatively healthy older adults living in rural communities.…”
Section: Discussionmentioning
confidence: 66%